Implementasi Dakwah Islamiyah di Era Milenial - Bachruddin, Rizal; Sitika, Ahmad Junaedi (Lembaga Yasin AlSys, 2022)
The purpose of writing is to convince and explain the implementation of Islamic da'wah in the millennial era. The writing method used is descriptive qualitative with a literature study approach. The results of the writing show that Islamic da'wah needs to be carried out by following the times and technology in this millennial era with the aim that preachers are more careful in utilizing millennial da'wah media to provide knowledge, understanding, and knowledge about Islam to Mad'u. The millennial era is an era where technology is developing so rapidly that it makes it easier for people to get information from various places in the world. This millennial era can be said to be the golden age of the millennial generation.